Uji Kinerja Turbin Angin Sumbu Vertikal Tipe Darrieus-H Naca 0018 Modifikasi Dengan Variasi Sudut Pitch 35 derajat,40 derajat,45 derajat,50 derajat,55 derajat,60 derajat - Prastiko, Yunika Cahyo, Nur Aklis, S.T., M.Eng, Wijianto, ST, M.Eng, Sc (2016)
Wind energy is the one of alternative energy that could be produced rapidly through natural processes. Wind energy could be converted into electrical energy by using wind turbine. Vertical axis wind turbine is a type of wind turbine that could spined out at low speed and was made with low costing. The performance of the wind turbine will be affected by the pitch angle and the additional of the flap on the airfoil NACA could be increase the lift force. The purpose of this research was to determine the power, the torque, the efficiency of the wind turbine, and also which one of the pitch angle most effectively to extracting energy. This research was conducted by using vertical axis wind turbine Darrieus-H NACA 0018 modified with using pitch angle 35 derajat,40 derajat,45 derajat,50 derajat,55 derajat,60 derajat. The performance of this wind turbin measured using wind tunnel type open circuit with wind speed 4,8 m/s and the weight load 250 gram. The result showed that the number of the pitch angle was affected the power and the efficiency of the wind turbine. In this research of vertical axis wind turbine darrieus-H NACA 0018 modification capable of generating power 0,859 Watt, With pitch angle 500, the torque 0,154 Nm and 4,90 % for the maximum efficiency. Keywords: Flap, NACA 0018 modification, pitch angle, vertical axis wind turbine Darrieus - H.